MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAMA (IPA) DENGAN PENERAPAN METODE DEMONSTRASI SISWA KELAS VI SD NEGERI 004 SIMPANG PULAI KECAMATAN UKUI - Esteruli Simanullang (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This study is a classroom action research aimed at improving science (IPA) learning outcomes at SD Negeri 004 Simpang Pulai. The background of this study is the low science learning outcomes, as observed from only 50% of students (11 out of 22) achieving completeness in their study results. The reasons for this include: (1) the teacher’s use of lecture-based methods; (2) teacher-centered learning; and (3) passive students who quickly become bored and lose motivation in subsequent lessons. Based on this situation, the researchers applied the demonstration method in learning. The research problem is formulated as follows: Can the application of the demonstration method improve science learning outcomes at SD Negeri 004 Simpang Pulai, Kecamatan Ukui? The purpose of this study is to enhance learning outcomes through the implementation of the demonstration method in science. This research was conducted over two cycles. The results indicate that the learning outcomes of science improved in each cycle. In the first cycle, the average score increased from 65 (initial data) to 69.25. In the second cycle, the average score further increased to 74.5. Based on these results, it can be concluded that the implementation of the demonstration method can effectively improve science learning outcomes at SD Negeri 004 Simpang Pulai, Kecamatan Ukui, Pelalawan.